Basics of energy balance of impact contact of metal shot with elastic-plastic half-space - Goryk, О.; Brykun, O.; Herashchenko, Ye.; Tykhonenko, V. (Scientific Progress & Innovations, 2024)
The study of abrasive wear processes, mechanical treatment of product surfaces in the construction, agricultural, and mechanical engineering industries by a mass high-speed jet (flow) of working solid particles for cleaning the surface layer or strengthening is based on one or another theoretical model of interaction between a separate spherical body (shot) and a deformable flat body (barrier). The barrier creates plastic resistance to penetration of the attacking ball. In this case, the physical nature of the phenomena of impact contact of a metal ball (shot) with an elastic-plastic half-space is of interest. The process still remains poorly understood. In particular, the relationship of these phenomena with the energy balance of the process, as the main criterion for influencing the results of the dynamic interaction of contacting bodies. An analysis of the energy balance of the interaction of a separate attacking shot with the surface of a metal half-space is proposed. This makes it possible to create reliable models for calculating and optimizing the main parameters of the impact of an air-abrasive torch (a mass of shots) on the state of free surfaces of products. Using the interaction diagram of the ball with a flat metal surface, it is possible to analytically determine the dynamic parameters of the mechanical properties of the metal being processed, given the normal force of the ball (pellet) impact on the attacked surface and the geometric dimensions of the dimple formed by the pellet, as well as the thermodynamic state of the local volume of the attacked body due to plastic deformation. The proposed physical model-diagram of the pellet impact on the treated surface, the essence of which is the rotational-translational motion of the pellet, makes it possible, based on the energy balance of the system, to determine the movement, speed, acceleration, as well as the forces of normal and tangential pressure of the pellet on the attacked surface during the formation of a trace (dimple), as well as the power consumption of the attacking pellet. The proposed model of impact when the pellet moves along the normal to the metal half-space, which has elastic and plastic properties, makes it possible to determine the dynamic parameters of the mechanical properties of the metal of a particular product. In this case, the initial data for performing analytical calculations are: the diameter of the sphere described around the pellet, the attack speed of the treated surface and the geometric dimensions of the groove.